1995
DOI: 10.1093/infdis/172.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Cellular and Humoral Immune Responses of a Booster Dose of Varicella Vaccine 6 Years after Primary Immunization

Abstract: Four hundred nineteen children and adolescents immunized with live varicella vaccine 4-6 years earlier were enrolled in a study to evaluate the safety and immune response to a booster dose containing approximately 3300 pfu of virus. Of the subjects, 99% (414/419) maintained antibody to varicella zoster virus (VZV) with a geometric mean titer of 25.7 and mean stimulation index (SI) for VZV-specific lymphoproliferation response of 40.3 +/- 5.3 (SE). Some 7-10 days after the booster immunization, seropositivity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 12 publications
2
38
1
Order By: Relevance
“…53 When a second dose of varicella vaccine is administered 4 to 6 years after the first dose, a rise in VZV-specific antibody concentrations occurs rapidly and overall VZV antibody concentrations achieved are comparable with antibody concentrations achieved when 2 vaccine doses are administered 3 months apart. 58 Varicella, measles, mumps, and rubella antibody concentrations after administration of a single dose of MMRV vaccine are comparable with concentrations after administration of MMR vaccine and monovalent varicella vaccine concomitantly at separate injection sites. 43 Among 5446 healthy children 12 to 23 months of age enrolled in 4 clinical trials, 91.2% achieved varicella antibody titers of Ն5 gpELISA units per mL (95% confidence interval: 90.3%-92%).…”
Section: Immunogenicitymentioning
confidence: 89%
“…53 When a second dose of varicella vaccine is administered 4 to 6 years after the first dose, a rise in VZV-specific antibody concentrations occurs rapidly and overall VZV antibody concentrations achieved are comparable with antibody concentrations achieved when 2 vaccine doses are administered 3 months apart. 58 Varicella, measles, mumps, and rubella antibody concentrations after administration of a single dose of MMRV vaccine are comparable with concentrations after administration of MMR vaccine and monovalent varicella vaccine concomitantly at separate injection sites. 43 Among 5446 healthy children 12 to 23 months of age enrolled in 4 clinical trials, 91.2% achieved varicella antibody titers of Ն5 gpELISA units per mL (95% confidence interval: 90.3%-92%).…”
Section: Immunogenicitymentioning
confidence: 89%
“…16 To address this issue, a second dose of varicella vaccine was routinely recommended in the United States beginning in 2006. 1 Studies have indicated that a second dose among children produces an improved humoral and cellular immune response [24][25][26] that correlates with improved protection against disease. 24,27 Therefore, the second dose has the potential to further increase the population immunity, also providing indirect vaccine protection for people with contraindications to vaccination.…”
Section: Figurementioning
confidence: 99%
“…A one-dose schedule has been shown to be highly effective in reducing severe disease, but breakthrough cases of mild varicella occur. Studies comparing immune responses following a one- or two-dose regime have shown that higher seroconversion rates and a higher antibody titer are achieved among subjects who receive two vaccine doses, regardless of the time interval between doses [5962]. Nevertheless, cost-effectiveness modeling of two- versus one-dose schedules, suggesting that addition of a second dose demonstrates unfavorable incremental cost-effectiveness, has been instrumental in informing Australia’s decision to implement a one-dose schedule [55,63].…”
Section: Story Of Varicella Vaccine Developmentmentioning
confidence: 99%